2019
DOI: 10.3390/polym11081361
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cellulose Nanocrystals: A Potential Fire Retardant for Polymer Composites

Abstract: The flammability of synthetic thermoplastic polymers has been recognized as an increasingly important safety problem. The goal of this study was to evaluate a green and safe fire-retardant system comprising of cellulose nanocrystals (CNC) and zinc oxide nanoparticles (ZnO). CNCs coated with nano ZnO were incorporated in the high-density polyethylene polymer (HDPE) matrix at different concentrations. Fire testing results of different formulations of HDPE containing 0.4 to 1.0% zinc oxide coated CNC exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Cellulose is a natural polysaccharide and consists of repeating units of monomer glucose connected through (1,4) beta D linkages. Plant biomass is composed of cells surrounded by primary and secondary cell walls.…”
Section: Cellulose Fibre Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose is a natural polysaccharide and consists of repeating units of monomer glucose connected through (1,4) beta D linkages. Plant biomass is composed of cells surrounded by primary and secondary cell walls.…”
Section: Cellulose Fibre Architecturementioning
confidence: 99%
“…Cellulose has been reported as the most abundant, naturally sourced biopolymer, with 150 billion tons produced yearly [ 1 ]. Plants mainly consist of cellulose, which provides them with their structural integrity.…”
Section: Introductionmentioning
confidence: 99%
“…14,46 With recent advancements in nanotechnology, nanosized zinc oxides are among the emerging high-value inorganic products with significant features, (such as, high catalyst effect, effective antibacterial properties, high UV absorption, high thermal and physical stability, and high heat capacity) that have many applications in different industries, such as, cosmetics, plastics, sensors, and semiconductors. [47][48][49] It is common to use high concentration of inorganic mineral fillers, such as, Al(OH) 3 up to 20 wt% to modify flame retardancy of polyvinyl chloride (PVC). 50 However, it is reported that the addition of only 0.635 wt% of ZnO and 9 wt% of Al(OH) 3 combination into PVC can significantly increase the LOI value of PVC nanocomposite (up to 30%).…”
Section: Zinc Oxidementioning
confidence: 99%
“…There are numerous reports on improved flame retardancy performance of commercial polymers in the presence of surface-modified cellulose nanocrystals or cellulose nanoparticles hybrids with other fire retardants. 49,[79][80][81] A 10 wt% of CNCs extracted with phosphoric acid hydrolysis has proven to increase the thermal stability of polylactic acid (PLA). 82 Phosphoric acid is well-known for its fire retardancy property.…”
Section: Cellulose Nanofibersmentioning
confidence: 99%
“…In the paper published by Bajwa, D.S. et al (2019), the addition of 1 wt.% crystal nanocellulose and nano ZnO particles (CNC-ZnO) lowered the total smoke release by 9%, compared to pure HDPE [ 193 ]. Sometimes the best effect considering smoke suppression is achieved when nano FRs are used in synergism with nano smoke suppression agents, which was described in the paper published by Zhou, K. et al (2016).…”
Section: Flame Retardant Chemistrymentioning
confidence: 99%